Disposal habits and microbial load of solid medical waste in sub-district healthcare facilities and households in Yilo-Krobo municipality, Ghana. - Fredrick Egbenyah; Emilia Asuquo Udofia; Jesse Ayivor; Mary-Magdalene Osei; John Tetteh; Patience B Tetteh-Quarcoo; Eric Sampane-Donkor (PLoS ONE, 2021)
The study aimed to assess disposal practices and quantify the microbial load present in SMW from ten sub-district level healthcare facilities and 385 households in Yilo Krobo municipality, Ghana. Disposal of solid medical waste (SMW) was assessed by questionnaire-based surveys, unstructured interviews and field observations. Microbiological analysis identified species and counts of bacteria present in SMW from both sources. Sociodemographic factors influencing the method of SMW disposal in households were evaluated using logistic regression analysis, with statistical significance set at p<0.05. Open burning (29%), burying (25%) and disposal at a dumpsite (49%) were common methods used by households to discard SMW. SMW disposal at a dumpsite was associated with age of respondents in households. Older people (50+ years) were three times more likely to place SMW in household waste later discarded at a dumpsite, compared to younger persons (20-30 years) [a0R, 95%CI = 3.37, 1.41-8.02]. In sub-district level healthcare facilities, open burning and burying were the most common methods used. Bacillus subtilis, Klebsiella pneumonia, Pseudomonas aeruginosa, Clostridium tetani, Enterococcus faecalis, Acinetobacter spp. Escherichia coli, Bacillus cereus and Enterococcus faecium) were bacteria identified in SMW recovered from both the healthcare facilities and the households. Klebsiella pneumoniae, Acinetobacter spp. and Clostridium tetani were found exclusively in untreated SMW generated in the healthcare facilities. Bacillus spp. and Pseudomonas spp. were found in one sample of treated SMW. The microbial load in SMW from healthcare facilities and households ranged from 0.036 x 103cfc/mg to 0.167 x 103 cfc/mg and from 0.118 x 103cfc/mg to 0.125 x 103cfc/mg respectively. This highlights the need for institutionalizing appropriate treatment methods in sub-district level facilities or strengthening the linkages with higher level facilities to ensure regular and adequate treatment of SMW. Public guidance on management of SMW generated in households which is context specific should also be provided.